Evidence for WW production from double-parton interactions in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2020)
A search forWWproduction from double-parton scattering processes using same-charge electron-muon and dimuon events is reported, based on proton-proton collision data collected at a center-of-mass energy of 13 TeV. The analyzed data set corresponds to an integrated luminosity of 77.4 fb-1, collected using the CMS detector at the LHC in 2016 and 2017. Multivariate classifiers are used to discriminate between the signal and the dominant background processes. A maximum likelihood fit is performed to extract the signal cross section. This leads to the first evidence for WW production via double-parton scattering, with a significance of 3.9 standard deviations. The measured inclusive cross section is 1.41 +/- 0.28 (stat) +/- 0.28 (syst) pb.